Loyalty [large type] - Scottoline, Lisa (Random House Large Print, 2023)
Franco Fiorvanti is a handsome lemon grower toiling on the estate of a baron. He dreams of owning his own grove, but the rigid class system of Sicily thwarts his ambition. Determined to secure a better future, Franco will do anything to prove his loyalty to the baron. But when the baron asks him to kidnap a little boy named Dante, Franco makes a decision that will change his life--and even the history of Sicily--forever.